Zein film functionalized atomic force microscopy and Raman spectroscopic evaluations on surface differences between hard and soft wheat flour. (January 2018) - Kwek, Jin W.; Siliveru, Kaliramesh; Cheng, Shuying; Xu, Qisong; Ambrose, R.P. Kingsly
Abstract: Fundamental differences exist between the surfaces of hard and soft wheat flours. Ranging from surface roughness, chemical composition to cohesive forces, these differences could affect the flow behaviour of wheat flour. In an attempt to address these differences, we developed a zein film functionalized atomic force microscopy technique to evaluate the surface forces on compacts of hard, soft wheat flour, and its pure components, starch and gluten. Using the pure wheat components as the baseline, we analyzed the chemical compositional differences via Raman spectroscopy coupled with Band–Target Entropy Minimization (BTEM ® ) algorithm. The zein film functionalization distinguishes between wheat starch and gluten with stronger interactions on starch at least twice that of gluten. In general, soft wheat flour has higher adhesion forces than hard wheat flour of the same particle size. Higher starch content at the expense of protein in soft wheat flour seems to suggest the difference. However, the microstructural difference of starch granules on the compacted surface could describe more adequately the effect of particle size on the interaction forces. Highlights: Developed zein film functionalized atomic force microscopy. Differentiated the surface force between starch and gluten. Quantified the adhesion force differences in soft and hard wheat flour. Raman with BTEM algorithm analyses the surface chemical composition of wheat flour.